Her night with the duke ebook - Quincy, Diana (Clandestine Affairs, 2024)
A widow unknowingly spends a hot night with her future son-in-law in this "unputdownable" Regency romance series debut ( Publishers Weekly , starred review). "A steamy Regency fraught with family discord as well as societal and racial prejudices . . . with an honorable hero and a spirited Anglo-Arab heroine who fights for acceptance and love on her own terms." — Library Journal (starred review) When Lady Delilah Chambers finds herself stranded at a country inn on a rain-swept evening, she's forced to fend off a group of ruffians with the help of a handsome gentleman. Irresistibly drawn to each other, Leela and the stranger spend one reckless night in each others' arms—and then go their separate ways. But the very next day Leela receives the shock of her life when she meets the duke who is set on wedding her beloved stepdaughter. One night isn't enough with a woman as fierce, fiery, and brilliant as Leela. Elliot Townsend, Duke of Huntington, cannot believe his good fortune when their chance encounter leads to an unforgettable evening of passion. Yet Hunt's luck runs out when he is introduced to his prospective mother-in-law. Dowagers aren't supposed to look like this . . .   Leela and Hunt are determined to keep each other at arm's length, which should be easy enough for two intelligent adults with reputations to uphold. The problem is all logic is lost when it comes to a passion that refuses to be ignored. "Leela and Hunt's amorous scenes are page-turners, but it's Quincy's extraordinary ability to convey complex emotions that sets the book apart. . . . An exciting start to a new Regency romance series which promises to highlight new voices from the era." — Kirkus Reviews (starred review)